Nature Experiences of Older People for Active Ageing: An Interdisciplinary Approach to the Co-Design of Community Gardens - Boffi, Marco; Pola, Linda; Fumagalli, Natalia; Fermani, Elisabetta; Senes, Giulio; Inghilleri, Paolo (Frontiers in Psychology, 2021)
In Western countries, the concepts of healthy ageing and active ageing, that is, concepts that favour health, participation, and security to increase the quality of life of older people, have become key issues. Hence, the effective design of public green spaces in urban areas is crucial, as visiting these areas encourages social relations and interactions in natural, healthy contexts. Consistent with these perspectives, existing landscape design criteria emphasise the importance of considering not only the functional and aesthetic elements, but also the ecosystemic and biophilic relationships between people and the environment, producing positive effects for both. To maximise the impact of such design criteria, proper engagement strategies are desirable, both to assign an active role to older people themselves and to inform the fine-tuning of the design process according to the specific needs of the local population. This study presents an interdisciplinary co-design method that encourages and informs a biophilic approach by describing the experiences of people in natural environments, actual and designed, through the application of attention restoration theory (ART). The case study was developed through six focus group meetings with older people for the co-design of a restorative area in a community garden in the Ortica district in Milan (Italy). Results show how the main needs expressed by participants can be classified into the ART factors of “compatibility” (a multifunctional garden), “fascination” (sense of contact with nature), and “being away” (metaphorical escape from nursing homes). The garden designed includes biophilic principles that respond to such needs, and specific links with designed elements were identified. For example, “being away” (e.g., isolation from daily routine and visual occlusion of the surroundings) and “compatibility” (e.g., pergola and aesthetic value) are the factors that include the elements that more satisfactorily answer previous needs. “Fascination” also includes many positive aspects, allowing space for improvements (e.g., more water elements, interaction with animals). Implications of the method are discussed, including the importance of subjective experience in informing design, the use of different psychological constructs to describe it, and the methodological alternatives for psychological assessment.